In their own words: Stories from HIV-positive African American women. (October 2017) - Robillard, Alyssa G; Reed, Cymone; Larkey, Linda; Kohler, Connie; Ingram, Lucy A; Lewis, Kaleea; Julious, Carmen
Objectives: African American women are disproportionately impacted upon by HIV, particularly in the Southern states of the USA where the percentage of new cases of HIV and the percentage of people living with HIV in the USA are highest. This study describes the lived experiences of HIV-positive African American women based on their written stories. Design: Naturalistic qualitative design. Setting: Three organisations serving people living with HIV in a Southern state in the USA. Method: HIV-positive African American women 18 years of age and older ( N  = 23) recruited from organisations working with people living with HIV were given the opportunity to write their own story following their participation in a semi-structured individual private interview. Content analysis was conducted on the written accounts. Results: Analysis of narratives written by HIV-positive African American women revealed themes of self-actualisation and self-worth. While some stories highlighted experiences of helplessness/hopelessness, most stories were more optimistic in nature, offering advice for prevention and highlighting individual efforts of advocacy and education. Stories also touched on risk/protective behaviour and women's acknowledgement of their own responsibility in their HIV status. Conclusion: Strengths and resources are expressed in stories, as well as the acknowledgement of stressors associated with HIV. These within-culture narratives may be useful in programmes and interventions to inform culturally resonant prevention efforts and promote self-management activities among women living with HIV.